2023
DOI: 10.1038/s41591-023-02503-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of bivalent and monovalent SARS-CoV-2 variant vaccines: the phase 2 randomized open-label COVAIL trial

Abstract: Vaccine protection against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection wanes over time, requiring updated boosters. In a phase 2, open-label, randomized clinical trial with sequentially enrolled stages at 22 US sites, we assessed safety and immunogenicity of a second boost with monovalent or bivalent variant vaccines from mRNA and protein-based platforms targeting wild-type, Beta, Delta and Omicron BA.1 spike antigens. The primary outcome was pseudovirus neutralization titers at 50% … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…Of the 28 studies we identified, only two studies 1,3 contained data that could be used to contribute to all four comparisons, however no study contained data for both the old and updated immunogens across all four comparisons. In addition, 1 study could not be used in our analysis as it did not include titres after one of the relevant immunogens 9 , leaving 27 studies that could contribute to one or more of the comparisons identified in Figure 2A.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the 28 studies we identified, only two studies 1,3 contained data that could be used to contribute to all four comparisons, however no study contained data for both the old and updated immunogens across all four comparisons. In addition, 1 study could not be used in our analysis as it did not include titres after one of the relevant immunogens 9 , leaving 27 studies that could contribute to one or more of the comparisons identified in Figure 2A.…”
Section: Resultsmentioning
confidence: 99%
“…Secondly, there were a limited number of studies 2,3,5,6,14,17,19,20,23,24 that provided a head-to-head comparison of in vitro neutralisaEon Etres elicited by different booster immunogens (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations